2017
DOI: 10.1038/s41598-017-05288-y
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of increasing typhoons on the structure and function of a subtropical forest: reflections of a changing climate

Abstract: Due to their destructive and sporadic nature, it is often difficult to evaluate and predict the effects of typhoon on forest ecosystem patterns and processes. We used a 21-yr record of litterfall rates to explore the influence of typhoon frequency and intensity, along with other meteorological variables, on ecosystem dynamics in a subtropical rainforest. Over the past half century there has been an increasing frequency of strong typhoons (category 3; >49.6 m s−1; increase of 1.5 typhoons/decade) impacting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 44 publications
(52 reference statements)
2
44
0
Order By: Relevance
“…Damages to trees may affect the level of foliar nutrient leaching and nutrient uptake by roots and thus the nutrient export . The poor correlation between maximum wind velocity and precipitation quantity reported by Lin et al (2011) suggests that precipitation quantity is not a good predictor of the magnitude of typhoon influences on nutrient input-output budget and likely contributed to the low predictability of discharge on ion budget during typhoon period.…”
Section: Unpredictability Of Hydrochemical Response To Climate Extremesmentioning
confidence: 95%
“…Damages to trees may affect the level of foliar nutrient leaching and nutrient uptake by roots and thus the nutrient export . The poor correlation between maximum wind velocity and precipitation quantity reported by Lin et al (2011) suggests that precipitation quantity is not a good predictor of the magnitude of typhoon influences on nutrient input-output budget and likely contributed to the low predictability of discharge on ion budget during typhoon period.…”
Section: Unpredictability Of Hydrochemical Response To Climate Extremesmentioning
confidence: 95%
“…landslides and debris 108 flows) within 2-3 days. These short-term, periodic, extreme events mobilize massive amounts of 109 terrestrial materials to the ocean (Kao et al, 2010;Huang et al, 2017). 110…”
Section: Methodsmentioning
confidence: 99%
“…Air-sea interactions have important implications in global warming. The global climate change affects the frequency and intensity of typhoons [34][35][36]. A multitude of recent studies have confirmed that the atmosphere is experiencing unprecedented warming as a result of human-caused emissions of carbon dioxide and other gases that absorb and trap heat in the atmosphere.…”
Section: Rainfall Mechanism Associated With Tropical Cyclonesmentioning
confidence: 99%